Association between enthesitis/dactylitis resolution and patient-reported outcomes in guselkumab-treated patients with psoriatic arthritis - Rahman, Proton; McInnes, Iain B.; Deodhar, Atul; Schett, Georg; Mease, Phillip J.; Shawi, May; Cua, Daniel J.; Sherlock, Jonathan P.; Kollmeier, Alexa P.; Xu, Xie L.; Sheng, Shihong; Ritchlin, Christopher T.; et al. (Clinical Rheumatology, 2024)
Objectives: To evaluate the association between enthesitis resolution (ER) and dactylitis resolution (DR) and meaningful improvements in patient-reported outcomes (PROs) among biologic-naïve patients with PsA receiving guselkumab in the DISCOVER-2 study. Methods: Enthesitis and dactylitis, characteristic lesions of PsA, were evaluated by independent assessors using the Leeds Enthesitis Index (range, 0–6) and Dactylitis Severity Score (range, 0–60). Proportions of patients with ER or DR (score = 0) among those with score > 0 at baseline were determined at weeks 24, 52, and 100. PROs included: fatigue (Functional Assessment of Chronic Illness Therapy-Fatigue [FACIT-Fatigue]), pain (0–100 visual analog scale), physical function (Health Assessment Questionnaire-Disability Index [HAQ-DI]), and health-related quality of life (36-item Short-Form Health Survey physical/mental component summary [SF-36 PCS/MCS]). Meaningful responses were defined as: improvements of ≥ 4 for FACIT-Fatigue, ≥ 0.35 for HAQ-DI, and ≥ 5 for SF-36 PCS/MCS and absolute scores of ≤ 15 for minimal pain and ≤ 0.5 for normalized HAQ-DI. Associations between ER/DR status and PRO response status were tested using a Chi-square test. Results: Guselkumab-treated patients with ER were more likely than those without ER to achieve minimal pain (p < 0.001), normalized HAQ-DI (p < 0.001), and PCS response (p < 0.05) at weeks 24, 52, and 100. Patients with DR were more likely than those without DR to achieve FACIT-Fatigue response at week 24 and week 52 (both p ≤ 0.01) and minimal pain at week 24 and normalized HAQ-DI at week 52 (both p ≤ 0.03). Conclusion: In biologic-naïve patients with active PsA treated with guselkumab, achieving ER or DR was associated with durable improvements in selected PROs, including those of high importance to patients. Trial registration: ClinicalTrials.gov (https://clinicaltrials.gov) NCT03158285; Registered: May 16, 2017. (Table presented.).
CRIS-Team Scopus Importer:2024-03-22
Keywords: Biologic; Dactylitis; Enthesitis; Guselkumab; Psoriatic arthritis